(untitled) - European Union Liaison Committee of Historians · Groupe de liaison des professeurs d'histoire contemporaine auprès de la Commission européenne · Historiker-Verbindungsgruppe bei der Europäischen Kommission (JEIH Journal of European Integration History, 2007)
The purpose of The Journal of European Integration History is to encourage the analysis and understanding of different aspects of European integration, especially since 1945, in as wide a perspective as possible. The Journal publishes the conclusions of research on diplomatic, military, economic, technological, social and cultural aspects of integration. Numbers devoted to single themes as well as to diverse subjects are published in English, French or German. Each number includes reviews of important, relevant publications. Website: www.zgei.nomos.de